Transformation of greek loanwords in coptic (with monastic rules of Pachomius and Shenoute as examples) - Natalia Golovnina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with the changes that Greek lexemes and their morphological forms undergo in the Coptic language. The study is based on the material of the monastic rules of Pachomius and Shenoute. The transformation of loanwords is systematised according to the main linguistic levels, i.e. phonetics, morphology, word formation, syntax and semantics. Spelling of loanwords that does not coincide with Greek can demonstrate not only the illiteracy of the scribe, but can also show attempts to put in the basis of the written form of words the phonetical rather than etymological principle. Greek words can take Coptic affi xes: vu,/ (sing.) — vu,ooue (pl.) ‘soul — souls’. Greek roots act as a building material for word formation on the models of the Coptic language: mntargoc (Copt. mnt + Greek argoc) ‘laziness, idleness’. A transition from one part of speech to another can also take place; thus, the nouns eidoc and tupoc (Greek εòδος, τύπος) in a certain syntactic environment act as indefi nite or negative pronouns. Particularly interesting is the adaptation of grammatical categories or forms that are absent from the Coptic language. For example, the Greek adjectives with three endings have only two forms in Coptic, namely masculine and neuter. In this case, there takes place a change of the grammatical category expressed, in that the animateness vs. inanimateness, rather than the gender, becomes the principle of agreement with the main word. The article pays special attention to the issue of semantic shifts in Greek loanwords as well as to the coexistence of synonyms with roots of both languages. The variety and productivity in the ways of assimilation of the foreign material testifies to the sophistication and fl exibility of the Coptic language.